Pengaruh Kesadaran Geopolitik Terhadap Sikap Kritis Mahasiswa Indonesia di Mesir atas Konflik Israel-Palestina - Edi Lukito -; Muhammad Jihan Muqaddas; Khotibul Khairi Al-Azizi; Yusril Firdaus Nuzula; Mawadatus Shalih (Jurnal ICMES, 2026)
This study explores the geopolitical awareness factors that influence the critical attitudes of Indonesian students in Egypt toward the Israeli-Palestinian conflict. The main subjects of this study are Indonesian students in Egypt. The Israeli-Palestinian conflict, a protracted dispute over territory and competing claims to sovereignty, has escalated again following the surprise attack carried out by Hamas on 7 October 2023, known as Operation Toofan Al-Aqsa. Since then, relations between the two sides have grown increasingly tense, with repercussions for geopolitical tensions across the Middle East and even the world. This study employs a mixed-methods approach with a convergent parallel design. This approach is used to measure the relationship between the awareness variables that influence the critical attitudes of Indonesian students in Egypt regarding the Israeli–Palestinian conflict, and is supported by the theory of awareness and the theory of critical attitude as the main variables of this study. Data were obtained through questionnaires and interviews with several Indonesian students in Egypt. The findings indicate that the geopolitical awareness of Indonesian students in Egypt is at a moderate level, while in understanding and responding to news related to the Israeli-Palestinian conflict they are categorized as not yet critical. The values, attitudes, and knowledge of Indonesian students in Egypt regarding Middle Eastern geopolitics are positively correlated with their critical attitudes toward the Israeli-Palestinian conflict.